Dow Chemical Company Allyn Point plant - Dow Chemical Company (1952)
General view of the exterior of the Dow Chemical Company Allyn Point plant located along the Thames River in Ledyard, Connecticut. As visible in the photograph, the plant, which produced Styrofoam, was located in an old rail terminal of the Norwich and Worcester Railroad.
Keywords: Railroad terminals; Industries; Dow Chemical Company